Determinants of Innovative Work Behaviorof MSME Employees during the Covid-19 Pandemic in Pematangsiantar City - Sudung Simatupang; Edy Dharma; Marthin Hutler Ambarita; Novita Butarbutar; Acai Sudirman (Sekolah Tinggi Ilmu Ekonomi AMM, 2022)
The main objective of this study is to determine the contribution of transformational leadership, psychological empowerment, and knowledge sharing to innovative work behavior. This study's research method includes library and field research design with a quantitative approach. The research subjects taken in this study were SME actors in the culinary sector in Pematangsiantar City. The research was carried out in eight sub-districts in Pematangsiantar City. Data collection techniques using observation, interviews, questionnaires, and documentation. The data analysis method used is Partial Least Square (PLS). The data analysis test tool uses the Smartpls statistical software. The results of the data analysis concluded that transformational leadership, psychological empowerment, and knowledge sharing positively and significantly affect innovative work behavior. The theoretical implication of this study concludes that aspects of knowledge sharing, psychological empowerment, and transformational leadership are important stimulants to encourage innovative work behavior. Furthermore, the managerial implications in this study conclude that aspects of knowledge sharing, psychological empowerment, and transformational leadership require serious attention for business actors to encourage more innovative work behavior.